Work Integrated Learning for Students : Challenges and Solutions for Enhancing Employability - Govender, Cookie; Våland, Terje I. (Cambridge Scholars Publishing, 2021)
Through work integrated learning (WIL), students, graduates, academics, businesses, employees, governments and communities are empowered to engage in lifelong learning, develop multidisciplinary skills; master technological applications, become a virtual employer or employee, become an entrepreneurial professional and expert, and integrate diversity consciousness into their lives. While individual, economic, community, national and global challenges abound in this regard, this book offers creative solutions that can radically shift perspectives, attitudes and beliefs. It encourages taking a lo.